The Effect of Pre‐Travel Advice on Sexual Risk Behavior Abroad: A Systematic Review. Issue 1 (3rd December 2013) - Croughs, Mieke; Remmen, Roy; Van den Ende, Jef
Abstract Background Travelers often have casual sex abroad and the risk of acquiring a sexually transmitted infection (STI) associated with casual travel sex is considered to be threefold higher compared to the risk of casual sex in the home country. Consequently, international guidelines recommend including STI advice in the pre‐travel consultation. We performed a systematic review on the effect of a pre‐travel STI intervention on sexual risk behavior abroad. Methods In September 2012, a systematic analysis and meta‐analysis of peer reviewed literature were performed on the relation between pre‐travel STI advice for travelers and sexual risk behavior abroad. Primary outcome measure consisted of the number of travelers with a new sexual partner abroad; secondary outcome measure entailed the proportion of consistent condom use. Results Six studies were identified for inclusion in the review, of which three clinical trials on the effect of a motivational intervention compared to standard pre‐travel STI advice qualified for the meta‐analysis. Two of these trials were performed in US marines deployed abroad and one in visitors of a travel clinic. The extensive motivational training program of the marines led to a reduction in sexual risk behavior, while the brief motivational intervention in the travel clinic was not superior to standard advice. The meta‐analysis established no overall effect on risk behavior abroad. No clinical trials on the effect of a standard pre‐travel STI discussion were found, but a cohort study reported that no relation was found between the recall of a nonstructured pre‐travel STI discussion and sexual risk behavior, while the recall of reading the STI information appeared to be related to more consistent condom use. Conclusions Motivational pre‐travel STI intervention was not found to be superior to standard STI advice, while no clinical trials on the effect of standard pre‐travel STI advice were found.